Quality Education, An Important Lesson For Challenging The Growth Of Society On The Perspective Of Christianity In Rongmei Community - Panmei Peter (Lembaga Sembilan Tiga Community, 2023)
Quality Education is an important factor in each and every human society where they are found. Education has most often been regarded as the spine of development. It is a challenging task for the growth of society. This work is mentioned from the contributions of Christianity and Rongmei in schooling in Rongmei tribe of Manipur. The paper analyses the quality of education on self -questionnaire as there is no reliable source. The data was analyse using Hinton (2004) cronbach’s alpha value (.5). If the number is greater or crosses the cut alpha of Hinton, quality education maintain among the Rongmei. Descriptive statistics, item scale and ANOVA were determined to find the result of quality education. Moreover, the data was positively significant as there is a Christianity follower, quality educations also maintain. Therefore, it is large in learn about for a perception into the function and responsibilities of religion towards education. In the case of Rongmei community, like other tribes, they have an effect on of faith on (formal) education has immensely ensured the development of individual lives, communities and traditional institutions in all the levels.